(untitled) (Orthodontic Journal of Nepal, 2024)
Introduction: Burstone’s analysis for orthognathic surgery, popularly known as COGS (Cephalometric for Orthognathic Surgery), is widely used for diagnosis and treatment planning of both orthognathic and orthodontic cases. Numerous studies have validated this analysis and determined values based on their ethnicities, demographic groups, population, and genders. This study aimed to determine the cephalometric norms in the Dogra ethnic population of Indo- Aryan origin, settled in the Jammu region, which is situated in the northern India. Materials & Methods: The subjects selected for this study comprised 50 males and 50 females of Dogra origin. Lateral cephalograms of subjects with Class I skeletal base were taken in a standardized way and traced manually. All tracings were performed by the same operator and the intra-class correlation coefficient was determined to account for error. The values for all landmarks specified in Burstone’s analysis were determined and compared with those of the Caucasian population. The collected data were tabulated in an Excel sheet and subjected to statistical analysis. Unpaired t-test was used to compare between both groups in relation to cephalometric parameters between Caucasian and Dogra males and females. Results: Most of the parameters in COGS showed statistically significant differences between Dogra males and females. Similarly, when the Dogra population values were compared with those of Caucasians, many parameters were found to be statistically different. Conclusion: The Dogra population exhibits statistically different skeletal and dental features compared to Caucasian norms.